Genetically supported causality between gut microbiota, gut metabolites and low back pain: a two-sample Mendelian randomization study - Su, Mengchan; Tang, Yidan; Kong, Weishuang; Zhang, Shuangyi; Zhu, Tao (Frontiers in Microbiology, 2023)
Background: Previous studies have implicated a vital association between gut microbiota/gut microbial metabolites and low back pain (LBP), but their causal relationship is still unclear. Therefore, we aim to comprehensively investigate their causal relationship and identify the effect of gut microbiota/gut microbial metabolites on risk of LBP using a two-sample Mendelian randomization (MR) study. Methods: Summary data from genome-wide association studies (GWAS) of gut microbiota (18,340 participants), gut microbial metabolites (2,076 participants) and LBP (FinnGen biobank) were separately obtained. The inverse variance-weighted (IVW) method was used as the main MR analysis. Mendelian randomization pleiotropy residual sum and outlier (MR-PRESSO) and MR-Egger regression were conducted to evaluate the horizontal pleiotropy and to eliminate outlier single-nucleotide polymorphisms (SNPs). Cochran’s Q-test was applied for heterogeneity detection. Besides, leave-one-out analysis was conducted to determine whether the causal association signals were driven by any single SNP. Finally, a reverse MR was performed to evaluate the possibility of reverse causation. Results: We discovered that 20 gut microbial taxa and 2 gut microbial metabolites were causally related to LBP (p < 0.05). Among them, the lower level of family Ruminococcaceae (OR: 0.771, 95% CI: 0.652-0.913, FDR-corrected p = 0.045) and Lactobacillaceae (OR: 0.875, 95% CI: 0.801-0.955, FDR-corrected p = 0.045) retained a strong causal relationship with higher risk of LBP after the Benjamini–Hochberg Corrected test. The Cochrane’s Q test revealed no Heterogeneity (p > 0.05). Besides, MR-Egger and MR-PRESSO tests showed no significant horizontal pleiotropy (p > 0.05). Furthermore, leave-one-out analysis confirmed the robustness of MR results. After adding BMI to the multivariate MR analysis, the 17 gut microbial taxa exposure-outcome effect were significantly attenuated and tended to be null. Conclusion: Our findings confirm the the potential causal effect of specific gut microbiota and gut microbial metabolites on LBP, which offers new insights into the gut microbiota-mediated mechanism of LBP and provides the theoretical basis for further explorations of targeted prevention strategies.